Applying Structural Equation Modeling to Measure Violence Exposure and Its Impact on Mental Health: Malawi Violence Against Children and Young Women Survey, 2013. Issue 3 (February 2021) - Fan, Amy Z.; Liu, Jin; Kress, Howard; Gupta, Sundeep; Shawa, Mary; Wadonda-Kabondo, Nellie; Mercy, James
This study examines exposure to multiple forms of violence among Malawian children and youth and their association with mental health outcomes. The Malawi Violence Against Children and Young Women Survey was conducted among a nationally representative sample of males and females aged 13 to 24 years ( n = 2, 162) in Malawi in 2013. The experience of sexual, physical, and emotional violence prior to age 18 and during the past 12 months and associated health outcomes were ascertained using a comprehensive interview. Latent factors of sexual violence, physical violence, and emotional violence as well as psychological distress were constructed. We examined whether the experience of violence was related to psychological distress after controlling for age and gender. Violence exposure prior to age 18 (early life) and during the past 12 months (proximal) were valid indicators for a latent factor representing overall lifetime violence exposure. Females were more likely to experience sexual violence, whereas males were more likely to experience physical violence. Experience of any type of violence decreased with age whereas experience of psychological distress increased with age. Current psychological distress was directly associated with exposure to sexual and emotional violence recently or during childhood. Exposure to multiple forms of violence during lifetime was related to two to seven folds higher odds of experiencing psychological distress compared with those who had never experienced violence. Future intervention strategies should address three forms of violence against children simultaneously in light of the associated adverse mental health outcomes.